Application of Lean Sigma to the Audiology Clinic at a Large Academic Center. (9th February 2016) - Huddle, Matthew G.; Tirabassi, Amy; Turner, Laurie; Lee, Emily; Ries, Kathryn; Lin, Sandra Y.
Abstract : Objective: To apply Lean Sigma—a quality improvement strategy to eliminate waste and reduce variation and defects—to improve audiology scheduling and utilization in a large tertiary care referral center. The project goals included an increase in utilization rates of audiology block time and a reduction in appointment lead time. Study Design: Prospective quality improvement study. Setting: Academic tertiary care center. Subjects: All patients scheduling audiology clinic visits July 2013 to July 2014. Methods: Value stream mapping was performed for the audiology scheduling process, and wasteful steps were identified for elimination. Interventions included a 2‐week block release, audiology template revision, and reduction of underutilized blocks. Schedule utilization and lead time for new patient diagnostic audiogram were measured for 5 months postintervention and compared with 5 months preintervention. Overall, 2995 preintervention and 3714 postintervention booked appointments were analyzed. Results: Block utilization increased from 77% to 90% after intervention ( P <. 0001). Utilization of joint‐with‐provider visits increased from 39% to 67% ( P <. 0001). Booked appointments increased from 2995 to 3714, with joint‐with‐provider booked appointments increasing from 317 to 1193. Appointment lead time averaged 24 days postintervention, compared with 29 days preintervention ( P =. 06). Average monthly relative value units measured 13, 321 preintervention and 14, 778 postintervention ( P =. 09). Conclusion: Lean Sigma techniques were successfully used to increase appointment block utilization and streamline scheduling practices.